MINIMIZING HEALTHCARE WORKER INVOLVEMENT IN BLOOD TRANSFUSION-ASSOCIATED INFECTIONS - Amal Sauod Mohammed Madkhli, Mana Yahya Saleh Al Zmanan, Yaser Yehya Alzamanan, Mohammed Salem Alharid, Dhafer Mahadi Hamad Al Saleem, Hadi Hussein Ali Binhamim, Hussain Zamel Hadi Al Mureeh, Mohammed Salem Alsulaiman, Mana Mahdi Hassan Alsagoor; Saleh Mohammed Al Qawban, Abdulaziz Saleh Al Mushraaf, Ahmad Qublan Hassan Al Atiq, Fahad Mahdi Mohammed Alghubari, Ali Mohammed Ali Al Mansour, Wafgah Mosleh Mubarak (Chelonian Research Foundation, 2023)
Introduction: Blood transfusions are essential for saving lives but carry the risk Of transmitting infections to patients and healthcare workers (HCWs). Despite advancements in blood safety, HCWs remain at risk of exposure to bloodborne pathogens during transfusion processes. This systematic review aimed to evaluate the effectiveness of intenentions designed to minimize healthcare worker involvement in blood transfusion-associated infections, focusing on the reduction of occupational exposure risks.. Methods: We conducted a comprehensive search of electronic databases, including PubMed, Embase, Cochrane Library, and Web Of Science, for interventional studies and clinical trials published up to 2022. The search terms used were related to blood transfusion, healthcare workers, and infection control among others. Studies were included if they were interventional and focused on reducing HCWs' exposure to transfusion-associated infections. The primary outcomes considered were the incidence Of needlestick injuries, exposure incidents, and infection rates among HCWs. Results: Twelve studies met the inclusion criteria. The interventions examined ranged from the implementation of safetyengineered needle devices and enhanced personal protective equipment (PPE) protocols to educational programs and technological innovations. The effectiveness of these interventions varied, with risk reductions reported between 50% to 80%. Notably, combined interventions that included educational components alongside practical safety measures were the most effective, demonstrating up to an 80% reduction in HO,Vs' risk of exposure to bloodborne pathogens. Conclusions: This review highlights the importance ofmultifaceted interventions in minimizing healthcare worker involvement in blood transfusion-associated infections. The findings suggest that combining educational programs with safety-engineered devices and technological innovations can significantly reduce occupational exposure risks. Implementing such comprehensive strategies is essential for enhancing the safety of blood transfusion practices and protecting healthcare workers from infection. Keywords: Blood Transfusion, Healthcare Workers, Infection Control, Occupational Exposure, Safety Interventions.